Proyeksi Kesenjangan Implementasi Revisi Undang Undang Desa - Fauzan Hidayat (Ministry of Home Affairs, 2025)
This study examines the gaps in the implementation of the revised Village Law (Law No. 3 of 2024) across Indonesia. A qualitative approach was employed to assess the experiences, perspectives, and interpretations of various stakeholders, including village governments, local communities, and experts in village administration. Through in-depth interviews, observations, and document analysis, the study identified factors that facilitated or hindered the implementation of the Village Law. The findings indicated that implementation challenges were largely driven by the inadequate capability of village government officials, limited access to financial and technical resources, and infrastructure disparities, particularly in underdeveloped regions such as Eastern Indonesia. These gaps impede equitable development and negatively affect the well-being of the village. The study emphasizes that enhancing the institutional capacity of the village, accelerating the development of basic infrastructure, and establishing a more integrated coordination strategy between central and regional governments are crucial. Furthermore, the study considers information technology a potential solution for increasing transparency and efficiency in village fund management. This study recommends implementing more responsive and adaptive policies to address regional needs, ensuring that the benefits of the revised Village Law are distributed equitably across Indonesia.